Understanding of and perceptions towards cardiovascular diseases and their risk factors: a qualitative study among residents of urban informal settings in Nairobi. Issue 6 (16th June 2019) - Wekesah, Frederick Murunga; Kyobutungi, Catherine; Grobbee, Diederick E; Klipstein-Grobusch, Kerstin
Abstract : Objectives: The study explored the understanding of and perception towards cardiovascular disease (CVD) and risk factors, and how they influence prevention and development of the conditions, care-seeking and adhering to treatment. Setting: Informal settlements of Nairobi. Participants: Nine focus group discussions consisting of between six and eight purposively sampled participants were conducted among healthy individuals aged 20 years or older. A total of 65 participants (41 female) were involved. Results: Poverty, ignorance and illiteracy promoted behaviours like smoking, (harmful) alcohol consumption, physical inactivity and unhealthy diet, implicated in the development of obesity, diabetes and hypertension. Some respondents could not see the link between behavioural risk factors with diabetes, hypertension and stroke and heart attacks. Contaminated food items consumed by the residents and familial inheritance were factors that caused CVD, whereas emotional stress from constant worry was linked to hypertension, stroke and heart attacks. Few and inadequately equipped public health facilities were hindrances to treatment seeking and adherence to treatment for CVD conditions. Lack of medication in public health facilities was considered to be the single most important barrier to adherence to treatment next to lack of family support among older patients. Conclusion: Interventions to prevent and manage CVD in low-resource and urban poor settings should consider perceptions and understanding of risk factors for CVD, and the interrelationships among them while accounting for cultural and contextual issues for example, stigma and disregard for conventional medicine. Programmes should be informed by locally generated evidence on awareness and opportunities for CVD care, coupled with effective risk communication through healthcare providers. Screening for and treatment of CVD must address perceptions such as prohibitive cost of healthcare. Finally, social determinants of disease and health, mainly poverty and illiteracy, which are implicated in addressing CVD in low-resource settings, should be addressed.